2021
DOI: 10.1111/nep.13996
|View full text |Cite
|
Sign up to set email alerts
|

End stage renal disease has an early and continuous detrimental effect on regulatory T cells

Abstract: End stage renal disease (ESRD) is followed by disturbed adaptive immunity, together with alterations in T cell subsets, including CD4+CD25+FoxP3+ cells (Tregs). In the present study, we assessed the effect of haemodialysis (HD) on the Treg population. CD3+CD4+, CD3+CD8+ and CD4+CD25+FoxP3+ cells were estimated by flow cytometry in 142 ESRD patients (45 ESRD-preHD, 97 on HD) and 30 healthy controls (HC). Patients on HD were classified into three groups according to time on dialysis (HD vintage -HDV): A < 2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…As for adaptive immunity, there is a prevalence of T helper 1 (Th1) responses, with end-stage kidney disease (ESKD) patients having a reduced CD4+/CD8+ T-cell ratio (to a degree because the numbers of naïve and memory CD4+ T-cells drop, while those of CD8+ memory T-cells rise). Moreover, there is an increase in the number of CD4+CD28highly differentiated T-cells and a decrease in regulatory T-cell (T-reg), naïve and central memory T-cell concentrations [28][29][30]. Alterations in the thymic function (possibly related to inflammation-induced lymphoid organ volume loss), which is normally responsible for the generation of the TCR repertoire and the control of autoreactive T-cells, are partially accountable for the changes observed in T-cell immunity.…”
Section: Alterations In T-lymphocytesmentioning
confidence: 99%
“…As for adaptive immunity, there is a prevalence of T helper 1 (Th1) responses, with end-stage kidney disease (ESKD) patients having a reduced CD4+/CD8+ T-cell ratio (to a degree because the numbers of naïve and memory CD4+ T-cells drop, while those of CD8+ memory T-cells rise). Moreover, there is an increase in the number of CD4+CD28highly differentiated T-cells and a decrease in regulatory T-cell (T-reg), naïve and central memory T-cell concentrations [28][29][30]. Alterations in the thymic function (possibly related to inflammation-induced lymphoid organ volume loss), which is normally responsible for the generation of the TCR repertoire and the control of autoreactive T-cells, are partially accountable for the changes observed in T-cell immunity.…”
Section: Alterations In T-lymphocytesmentioning
confidence: 99%
“…We have previously estimated phenotypic alterations of T and B lymphocytes in patients with end-stage renal disease (ESRD), at pre-dialysis stage, on dialysis treatment, and after renal transplantation [12][13][14][15]. The effect of ESRD on the immune phenotype proved to be unique; similar to senescence, albeit with substantial differences [12].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired innate immunity in HD patients may result in higher cytokine production against SARS-CoV-2 and induce a greater memory T cell response. Regulatory T cells, which are responsible for counteracting the overactivation of the immune response by producing IL-10, decrease with increasing HD vintage in HD patients [ 21 ]. However, a previous study demonstrated that COVID-19-infected HD patients have higher numbers of CD39+ regulatory T cells than COVID-19-infected control patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%